Persepsi Peran Account Representative pada Tingkat Kepatuhan Wajib Pajak - Amilin, A; Anisah, Nina (Jurnal Trikonomika, 2008)
At the past, organization structure of Directorate General of Taxation based on tax type. The implementation of that organization caused inefficiency and unoptimalized services. In four last years Directorate General of Taxation have reformed and modernized administration which emphasized on role of Account Representative as liaison officer who gives service, consults and control to taxpayer. The objective of this research is to analyze perception of the role of Account Representative that influences the tax payer compliance. The role of Account Representative is: (1) servicing, (2) consulting, and (3) monitoring. The data is compiled through distributing the questionnaire to 40 Account Representative as respondents. This questionnaire used to value the perception of the role of Account Representative at KPP Pratama Jakarta Gambir Dua. The multiple linear regression analysis, validity test, reliability test, F-test, t-test, also classical assumptions of regression are used to analyze data. The result of this research show that: (1) servicing significant influence with tax payer compliance, (2) consulting no significant influence with tax payer compliance, (3) monitoring no significant influence with tax payer compliance, (4) there are no significant influence between servicing, consulting, and monitoring with taxpayer compliance.